Botulinum toxin B suppresses the pressure ulcer formation in cutaneous ischemia-reperfusion injury mouse model: Possible regulation of oxidative and endoplasmic reticulum stress. Issue 2 (May 2018) - Sekiguchi, Akiko; Motegi, Sei-ichiro; Uchiyama, Akihiko; Uehara, Akihito; Fujiwara, Chisako; Yamazaki, Sahori; Perera, Buddhini; Nakamura, Hideharu; Ogino, Sachiko; Yokoyama, Yoko; Akai, Ryoko; Iwawaki, Takao; et al.
Highlights: BTX-B suppressed pressure ulcer formation in cutaneous I/R injury mouse model. BTX-B injection prevented the reduction of blood vessels by cutaneous I/R injury. BTX-B suppressed cutaneous I/R injury-induced hypoxia, oxidative stress and apoptosis. BTX-B suppressed oxidant-induced oxidative stress in ECs and fibroblasts in vitro . BTX-B suppressed cutaneous I/R injury-induced endoplasmic reticulum (ER) stress. Abstract: Background: We previously identified that botulinum toxin A (BTX-A) suppressed pressure ulcer (PU) formation after cutaneous ischemia-reperfusion (I/R) injury; however, regulation of cutaneous I/R-induced oxidative and endoplasmic reticulum (ER) stress by BTX-B was not investigated. Additionally, the efficacy of BTX-B injection has never been examined. Objective: Objective was to assess the effects of BTX-B on the formation of PU by cutaneous I/R injury, and the regulation of oxidative and ER stress in I/R injury by BTX-B. Methods: BTX-B was subcutaneously injected into I/R area, and wound size, vascular damage, hypoxic area, and apoptotic cells in I/R area were analyzed. We evaluated the extent of oxidative and ER stress in I/R area by using OKD48 mice and ERAI mice, respectively, which enabled evaluating oxidative and ER stress through bioluminescence detection. Results: BTX-B injection significantly suppressed the formation of PU by cutaneous I/R injury. Cutaneous I/R-induced vascular damage, hypoxic area, and number of oxidative-damaged cells and apoptotic cells were suppressed by BTX-B injection. BTX-B administration significantly inhibited I/R-induced oxidative stress signal in OKD48 mice. BTX-B reduced the I/R-induced oxidative stress-associated factors. BTX-B significantly inhibited the oxidant-induced reactive oxygen species and apoptosis of endothelial cells and fibroblasts. BTX-B significantly inhibited I/R-induced ER stress signal in ERAI mice. Cutaneous I/R injury-induced ER stress-response factors and GRP78/BiP and CHOP-positive cells in I/R area were significantly decreased by BTX-B injection. Conclusion: BTX-B injection might have protective effects against PU formation after cutaneous I/R injury by reducing vascular damage, hypoxia-induced oxidative and ER stress, and apoptosis.